(untitled) (Rainbow Journal, 2019)
This paper presents a narrative inquiry into a school administrator of a high school in Kathmandu. The objectives of the study were to explore how an administrator makes meanings of his leadership practice and why he enacts leadership the way he does. Using narrative inquiry as a research method and intersecting the narrative analysis by drawing on Bush’s (2010) three dimensions of leadership, the researcher evaluated Rupak’s role as an administrator, made meaning of his perceptions and contested his assumed responsibilities with the responsibilities he has been assuming. Among the three leadership dimensions – influence, values and vision, it was perceived from the participant’s personal practical experience that all three dimensions did not emerge in a linear sequence. Values and vision may be the driving force of the participant’s leadership practice whereas influence may or may not be intentional. By bringing forth the participant’s first-hand accounts it is hoped that the findings will facilitate to generate a new understanding of educational leadership, management and administration, gain an insight into the reconceptualization of leadership and may have useful implications for those who are taking up a new role of an organization, be it fledging or well-established, to excel themselves.